Corticosteroid therapy in patients with severe COVID-19 (Research, Society and Development, 2021)
The world panorama of disseminating the new coronavirus SARS-CoV-2 is considered a pandemic by the World Health Organization (WHO) with the risk of complications due to the imbalance of immune responses. The present study evaluated whether the use of corticosteroids has scientifically proven efficacy in treating patients with the severe form of COVID-19. It was a cross-sectional and integrative literature review from December 2019 to November 2020 after researching the PubMed, Scopus, Embase, Web of Science, and Google Scholar databases. According to the studies analyzed, positive results of corticotherapy were observed in patients with SARS-CoV-2 in the severe form of the disease. It was concluded that steroids are not indicated in the mild form of COVID-19 unless they have other comorbidities, such as chronic obstructive pulmonary disease (COPD) or asthma. Glucocorticoid therapy is relevant in the severe form of SARS-CoV-2, with short-term management and low doses being beneficial. It reduces morbidity and mortality and the length of stay in the ICU.